Environmental quality of an urban sub-basin: a study case of Alfenas – MG - Costa, Danilo Augusto Toledo; Guiçardi, Augusto César Ferreira; Sardinha, Diego de Souza; Mincato, Ronaldo Luiz (Ciência e Natura, 2018)
The cities expansion conditioned by the urban population increase exerts considerable ecosystems pressure, often leading them to high degradation stages. The use of proceedings and techniques that evaluate current conditions and possible future scenarios are indispensable, seeking sustainability for socioeconomic development and environmental protection. Therefore, a Rapid Assessment Protocol was applied to evaluate parameters of urban environmental and water quality of the Córrego do Pântano 1 Hydrographic Sub-basin, Alfenas - MG, located at the municipality periurban limit, important area for the provision of environmental services and a response indicator to the urban processes on the natural environment. Thus, weights were distributed for the environmental quality indicators and, for each variable, was designated a note, making possible the composition of a scenario of the environmental conditions of the studied sites. It was verified that the application of the Rapid Assessment Protocol is an efficient means for directing public policies aimed at mitigating the impacts caused by cities on the environmental and water quality of sub-basins under urban influence. It is recommended the implementation of a sub-basin management plan with guidelines that embrace the conservation of the area mainly directed to the recovery of native vegetation and inspection of the urban effluents emission.